The Midlands Liver Research Alliance - A partnership to optimise obesity-related liver disease research: targeting areas of high incidence and underserved communities [version 1; peer review: 2 approved] - Guruprasad Aithal; James King; Scott Willis; Louisa Herring; Kerry Hulley; Dimitris Papamargaritis; Melanie Davies (NIHR Open Research)
Background The prevalence of liver disease is rising in the United Kingdom (UK), with obesity underpinning surging metabolic dysfunction-associated steatotic liver disease (MASLD). MASLD is associated with an increased cardiometabolic risk, particularly when co-existing with type 2 diabetes. Progression to metabolic dysfunction-associated steatohepatitis (MASH) with hepatic fibrosis represents a clinical milestone strongly linked to serious liver disease and mortality. Therefore, clinically meaningful and sustained weight loss (≥10%) is a primary therapeutic target for patients with MASLD. Unfortunately, this is difficult for most people who adopt traditional lifestyle approaches. However, new obesity pharmacotherapies hold promise in MASLD, given their ability to produce dramatic weight loss (10–25%) and improve cardiometabolic health. Questions remain about the ability of these agents to improve liver fibrosis and patient-reported outcomes/quality of life in patients with advanced liver disease. Methods Led from the Midlands (UK) but with national representation, we developed a network of stakeholders (clinicians, academics, third-sector, industry, and PPIE representatives) with an interest in obesity-related liver diseases. This network was called the Midlands Liver Research Alliance (MLRA), which sought to 1) establish a PPIE stakeholder network, 2) identify research priorities, and 3) map the network infrastructure and expertise. Health inequalities within liver disease are a core priority within the MLRA. Results The MLRA developed a large PPIE stakeholder network in collaboration with other local liver partnerships. These networks facilitated the identification of key research priorities that led to three NIHR funding applications. Priorities centered around: 1) the importance of patient-centered outcomes in obesity-related liver disease research; 2) the potential of glucagon-like peptide 1 (GLP-1)-based obesity pharmacotherapy in alcohol use disorder; and 3) early identification and management of liver disease in primary care/community. Conclusions The MLRA has created a multidisciplinary hub of research expertise in obesity-related liver disease. This foundation provides a springboard for research activities in this area.